microRNA-223 Deficiency Exacerbates Acute Inflammatory Response to Monosodium Urate Crystals by Targeting NLRP3 - Yang QB; Li LQ; Zhang QB; He YL; Mi QS; Zhou JG (Dove Medical Press, 2021)
Qi-Bin Yang,1,2 Ling-Qin Li,1 Quan-Bo Zhang,2,3 Yong-Long He,1 Qing-Sheng Mi,2 Jing-Guo Zhou4 1Department of Rheumatology and Immunology, Affiliated Hospital of North Sichuan Medical College, Nanchong, 637000, Sichuan Province, People’s Republic of China; 2Henry Ford Immunology Program, Departments of Dermatology and Internal Medicine, Henry Ford Health System, Detroit, MI, 48202, USA; 3Department of Gerontology, Affiliated Hospital of North Sichuan Medical College, Nanchong, 637000, Sichuan Province, People’s Republic of China; 4Department of Rheumatology and Immunology, Clinical Medical College and The First Affiliated Hospital of Chengdu Medical College, Chengdu, 610500, Sichuan Province, People’s Republic of ChinaCorrespondence: Qing-Sheng MiHenry Ford Immunology Program, Departments of Dermatology and Internal Medicine, Henry Ford Health System, 1 Ford Place, Detroit, MI, 48202, USATel +1-313-876-1017Email qmi1@hfhs.orgJing-Guo ZhouDepartment of Rheumatology and Immunology, Clinical Medical College and the First Affiliated Hospital of Chengdu Medical College, Chengdu, 610500, Sichuan Province, People’s Republic of ChinaTel +86-28-8301-6078Email jgzhou@cmc.edu.cnObjective: MicroRNAs were identified as master-switch molecules limiting acute inflammatory response. This study investigated the potential role of microRNA (miR)-223 in the mechanism of gout.Methods: Wild-type (WT) and miR-223 knock-out (KO) mice were used to evaluate the phenotypes of gout models. Inflammatory cytokines were measured in air pouch and peritoneal cavity lavage fluid. In addition to miR-223 level in gout patients, miR-223 and pro-inflammatory genes were examined in bone marrow-derived macrophages (BMDMs) from mice as well as peripheral blood mononuclear cells from healthy controls (HC) treated with monosodium urate (MSU) crystals in vitro.Results: MiR-223 was up-regulated in the early phase in BMDMs from WT mice after MSU challenge and decreased rapidly, and this was not observed in miR-223 KO mice in vitro. In addition, miR-223 was required for macrophages homeostasis. In comparison with WT mice in vivo, miR-223 deficiency exacerbated swelling index of MSU-induced inflammation in foot pad and ankle joint models. MiR-223 deficiency also markedly aggravated inflammatory cells infiltration and cytokines release including interleukin (IL)-1β, IL-6 and monocyte chemotactic protein-1 (MCP-1) in the air pouch and peritonitis models. In the in vitro experiments, miR-223 deficiency promoted the inflammatory response by targeting NLR family pyrin domain containing protein 3 (NLRP3). Besides, miR-223 level was down-regulated in gout patients and in HC exposed to MSU in vitro.Conclusion: MiR-223 was down-regulated in gout patients and miR-223 deficiency exacerbated inflammatory response in diverse murine models, suggesting that up-regulation of miR-223 could be a potential therapeutic strategy for alleviating gouty inflammation.Keywords: miR-223, gout, animal models, cytokines, monosodium urate